PENINGKATAN SUMBER DAYA MANUSIA (SDM) DI BIDANG TEKNOLOGI INFORMASI BAGI KADER POSYANDU DESA SIRNOBOYO KABUPATEN WONOGIRI - Retno Tri Vulandari; Sri Harjanto; Sri Siswanti; Setiyowati Setiyowati; Hendro Wijayanto; Andriani Kusumaningrum; Didik Nugroho (Sekolah Tinggi Ilmu Ekonomi AMA, 2023)
Improvement of Human Resources (HR) is an effort made to form quality human beings with skills, work abilities and work loyalty to an organization or government. The flow of technology and information as well as the mobility of human resources from one place to another. One of the HR improvements that must be done is through training, education, and coaching. Information technology is a concept where certain objects have the ability to transfer data over a network without requiring human-to-human or human-to-computer interaction. Sirnoboyo Village, Giriwoyo District, Wonogiri Regency. The purpose of raising the theme of improving human resources in the field of information technology for posyandu cadres and village officials is to provide insight and improvement on the basis for using Ms. Word and digital form creation with Google - Forms. The method of implementing the service includes a basic computer workshop using Microsoft Office 2013. Then a workshop on improving the ability of posyandu cadres in making digital forms using Google-Form. The resulting output is the implementation of a workshop and an increase in the capacity of Sirnoboyo village human resources, namely posyandu cadres and village officials. At the end of this program, activities will be published through print and online media. Keywords: Human Resources, Posyandu Cadres, Digital Forms.